1996
DOI: 10.3109/00498259609052493
|View full text |Cite
|
Sign up to set email alerts
|

β-Apo-8′-carotenal, but not β-carotene, is a strong inducer of liver cytochromes P4501A1 and 1A2 in rat

Abstract: 1. The catalytic activities of several phase I and II xenobiotic-metabolizing enzymes and their immunochemical detection have been investigated in liver microsomes and cytosol of the male rat, which had been fed for 15 days with diets containing 300 mg/kg beta-carotene isomers (all-trans beta-carotene or beta-carotene from Dunaliella salina rich in 9-cis isomer or isomerized beta-carotene), or apocarotenoids as beta-apo-8'-carotenal, ethyl beta-apo-8'-carotenoate and citranaxanthin. 2. Beta-carotene, either al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(29 citation statements)
references
References 32 publications
0
29
0
Order By: Relevance
“…Excentric cleavage oxidative metabolites of ␤-carotene may also be associated with carcinogenesis through their induction of cytochrome P 450 enzymes, which can convert protocarcinogens into activated carcinogens, facilitate lipid peroxidation, or enhance RA catabolism, thereby diminishing retinoid signaling (18). For example, ␤-apo-8Ј-carotenal was shown to be a strong inducer of cytochrome P 450 enzymes (17). Several studies have shown that ␤-apo-carotenals inhibit mitochondria respiration and elevate the accumulation of mal- ondialdehyde in vitro (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…Excentric cleavage oxidative metabolites of ␤-carotene may also be associated with carcinogenesis through their induction of cytochrome P 450 enzymes, which can convert protocarcinogens into activated carcinogens, facilitate lipid peroxidation, or enhance RA catabolism, thereby diminishing retinoid signaling (18). For example, ␤-apo-8Ј-carotenal was shown to be a strong inducer of cytochrome P 450 enzymes (17). Several studies have shown that ␤-apo-carotenals inhibit mitochondria respiration and elevate the accumulation of mal- ondialdehyde in vitro (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…Bilrubin was the first endogenous ligand discovered but was very weak in generating AhR-mediated CYP1A1 induction [Sinal and Bend, 1997]. Plant carotinoid indole-3-carbinol was also a potent ligand for AhR [Bjeldanes et al, 1991;Gillner et al, 1993;Gradelet et al, 1996].…”
Section: Tryptophan Metabolites and Ahrmentioning
confidence: 99%
“…The rather weak effect of bixin on rat liver monooxygenases belonging to the CYP1A subfamily, on the other hand, indicated that this carotenoid, like ß-carotene, lycopene and lutein, does not share the potent CYP1A1/2-inducing properties of apoor oxocarotenoids such as ß-Apo-8'-carotenal, canthaxanthin and astaxanthin (6,7). The mechanism underlying CYP1A induction by carotenoids is still unclear.…”
mentioning
confidence: 99%